Architektura sociálně vyloučených - vězení s ostrahou v Brně - Kanderová, Denisa (Vysoké učení technické v Brně. Fakulta stavební, 2013)
Funkčný betónový objekt zjednotený betónovou mrežou. Druhá čistá hmota haly. Oba objekty spojené lávkou naväzujúcou na centrálnu chodbu.

Functional concrete building united by concrete grid. The second clear mass hall. Both buildings connected by footbridge a joined the central hallway.
Architecture of socially excluded - Higher security prison in Brno
Keywords: betón; mreža; raster; funkčnosť; jednoduchosť; bezpečnosť; concrete; grid; functionality; simplicity; safety